Study on the failure behavior of saturated sandstone based on AE and avalanche characteristics - Xiancheng Zhou; Jiao Wang (Scientific Reports)
Abstract Sandstone, a commonly distributed geological material, is critical to the safety of engineering structures such as mine tunnels, dams, and tunnels, particularly in terms of its mechanical properties and failure mechanisms under saturated conditions. This study investigates the influence of water on the failure characteristics of yellow sandstone using acoustic emission (AE) technology and avalanche dynamics. The results show that in the saturated state, the uniaxial compressive strength, elastic modulus, and peak strain of yellow sandstone decreased by 40.07%, 26.44%, and 22.32%, respectively. AE energy, count, and cumulative energy were reduced, and changes in the r value indicated variations in internal fractures. RA-AF-based fracture type statistics revealed that the proportion of tensile cracks increased from 18.66 to 45.57% under saturation. This suggests that moisture promotes the formation of tensile cracks, resulting in a more complex failure mode. The failure of yellow sandstone followed avalanche-like characteristics, with AE energy release displaying a power-law distribution and waiting times exhibiting a double power-law distribution, conforming to the mean-field force integration model. The mean-field indices (ε, τ′, α, x, χ) increased in the saturated state. Avalanche modeling showed that water caused a more dispersed energy release during crack propagation, with AE signals revealing more low-energy events.